Kewenangan Dinas Lingkungan Hidup dalam Upaya Pengendalian Pencemaran Laut di Pantai Teluk Labuan Berdasarkan Peraturan Daerah Kabupaten Pandeglang Nomor 4 Tahun 2016 tentang Pengelolaan Sampah - Inisa Alfath Amara; Mohamad Fasyehhudin; Ahmad Lanang Citrawan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The problem of waste along the coast of Teluk Labuan – Banten continues to be a concern because it is dominated bt household waste. This is caused by the behavior of the local people who like to throw garbage on the banks of rivers and beaches in the hope that the trash will be carried by the currents into the sea. This problem results in sea water pollution and will certainly threaten the diversity of marine life and public health. This study aims to examine the authority of the Pandeglang Regency Environmental Service in managing household waste as an effort to control marine pollution on the fishing port beach fo Teluk Labuan – Banten based on Regional Regulation of Pandeglang Regency Number 4 of 2016 concerning Waste Management and what obstacles it faces. This study uses a juridical-empirical research method. Based on the results of the study, the authority of the Pandeglang Regency Environmental Service in accordance with its main tasks and functions has delegation authority and responsibility in carrying out government tasks in the field of waste management in the Pandeglang Regency area. There are at least 5 (five) inhibiting factors that are felt by the Office in implementing waste management, including low participation and awareness of the community due to the habit of throwing garbage in rivers and coastal areas, limited budget for implementing waste management, lack of facilities and infrastructure, limited resources human resources in internal agencies, and weak law enforcement in society. The input given can be in the form of increasing the active role of the Office in the form of campaigns, counseling, outreach, coaching, supervision and control of waste management, as well as increasing the emphasis on enforcement of environmental law on waste management. In addition to improving waste management infrastructure facilities, reshuffling waste management in accordance with national standards with the 3R principle